2000
DOI: 10.1126/science.289.5477.284
|View full text |Cite
|
Sign up to set email alerts
|

Global Water Resources: Vulnerability from Climate Change and Population Growth

Abstract: The future adequacy of freshwater resources is difficult to assess, owing to a complex and rapidly changing geography of water supply and use. Numerical experiments combining climate model outputs, water budgets, and socioeconomic information along digitized river networks demonstrate that (i) a large proportion of the world's population is currently experiencing water stress and (ii) rising water demands greatly outweigh greenhouse warming in defining the state of global water systems to 2025. Consideration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
2,460
2
49

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 4,192 publications
(2,545 citation statements)
references
References 7 publications
34
2,460
2
49
Order By: Relevance
“…Physical water scarcity is reached when withdrawals of blue water exceed 5,000 -6,000 km 3 yr -1 (Raskin et al 1997;Vörösmarty et al, 2000;deFraiture et al 2001). Based on the global assessments of impacts of global green and blue water use (see Supplementary Discussion 4), we estimate that transgressing a boundary of ~4,000 km 3 yr -1 of consumptive blue water use (with a zone of uncertainty of 4,000 -6,000 km 3 yr -1 ) will significantly increase the risk of approaching green and blue water-induced thresholds (collapse of terrestrial and aquatic ecosystems, major shifts in moisture feedback and freshwater/ocean mixing) at regional to continental scales.…”
Section: Global Freshwater Usementioning
confidence: 99%
“…Physical water scarcity is reached when withdrawals of blue water exceed 5,000 -6,000 km 3 yr -1 (Raskin et al 1997;Vörösmarty et al, 2000;deFraiture et al 2001). Based on the global assessments of impacts of global green and blue water use (see Supplementary Discussion 4), we estimate that transgressing a boundary of ~4,000 km 3 yr -1 of consumptive blue water use (with a zone of uncertainty of 4,000 -6,000 km 3 yr -1 ) will significantly increase the risk of approaching green and blue water-induced thresholds (collapse of terrestrial and aquatic ecosystems, major shifts in moisture feedback and freshwater/ocean mixing) at regional to continental scales.…”
Section: Global Freshwater Usementioning
confidence: 99%
“…There are multiple stressors on this valuable resource (Heathwaite, 2010), including those on both water quantity (Vorosmarty et al, 2000) and quality (Onda et al, 2012;Seitzinger et al, 2010). In the future, these pressures will continue to increase, with larger populations making greater demands for food production, and, consequently, more intensive farming practices.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, climate change may even be speeded up in the future, consequently leading to an increase in probabilities of floods and droughts. Therefore, changes in water resources and the underlying driving forces due to climate changes have become research focuses (Andréasson et al, 2004;Christensen and Lettenmaier, 2007;Frederick and Major, 1997;Gül et al, 2010;Lins and Slack, 1999;Liu and Cui, 2009;Null et al, 2010;Piao et al, 2007;Thodsen, 2007;Vörösmarty et al, 2000;Xu et al, 2010;Zhang et al, 2001). Andréasson et al (2004) discussed the impacts of climate change on streamflow under three anthropogenic CO 2 emission scenarios with a hydrology model (HBV) and concluded that the influences of climate change based on hydrology cycle varied geographically.…”
Section: S L Sun Et Al: Past and Future Changes Of Streamflow In Pmentioning
confidence: 99%